Bilberries: Curative and Miraculous – A Review on Bioactive Constituents and Clinical Research - Vaneková, Zuzana; Rollinger, Judith M. (Frontiers in Pharmacology, 2022)
Bilberry (Vaccinium myrtillus L.) fruits are an important part of local diets in many countries and are used as a medicinal herb to treat various disorders. Extracts from fruits are often a part of eye health-promoting supplements, whereas extracts from leaves are advertised for type 2 diabetes mellitus and glycemic control. This review provides an overview of the current knowledge of the phytochemical contents of bilberry fruits and leaves and their bioactivities, critically summarizes origins of the health claims and the outcome of clinical trials, with special attention towards those published in the past ten years. Overall, the three most referenced indications, which are type 2 diabetes mellitus, vision disorders and circulatory diseases, all include contradictory results with no clear conclusion as to the benefits and recommended dosages. Moreover, the indications for vision disorders and diabetes originate from unproven or false claims that have been repeated in research since the 20th century without consistent fact-checking. Beneficial clinical results have been attested for the treatment of dyslipidemia and chronic inflammatory disorders when applied as dietary supplementation of fresh bilberries or as anthocyanin-rich bilberry fruit extracts. However, there is a general lack of double-blinded controlled research with larger sample sizes.